NEW METHODS OF TEACHING THE HISTORY OF THE STATE AND THE LAW OF FOREIGN COUNTRIES - Varava, Iryna; Sukhodolska, Anastasiia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
The article is devoted to the issue of applying the latest methods, forms and innovative technologies of teaching the competitive lawyers. The role of teaching methods containing an innovative component is clarified. The methods of problem-based learning are determined as the priority in the professional training of future lawyers. The main problems arising in the educational process of training future lawyers, taking into account that teachers of higher legal education institutions are called upon to prepare professionals in the field of jurisprudence, who are competitive and capable of effective work in a post-industrial society. The study also highlights the need to change approaches to the teaching of legal disciplines, including such discipline as the history of the state and the law of foreign countries. The need for the use in the process of teaching the history of the state and the law of foreign countries of the latest services and instruments for training, educational platforms, mobile applications, the use of educational blogs, distance learning courses, platforms on the YouTube channel, a modern base of educational electronic resources designed to actively serve students and teachers is proven. The development of public relations, world globalization processes and rapid scientific and technological progress led to the transition to an information society, where the most important products are innovations and knowledge, which, in turn, become the main working resources of the country. Professional standard and educational programs provide for the formation of the key competences of future lawyers by the scientific and pedagogical workers of institutions of higher education. However, the formation of such abilities is a serious challenge for the teachers of higher education institutions. The inconsistency of the content and methods of educational activities of students with the changing features of professional activity, which are typical for the modern socio-economic and political conditions, remains an unsolved task for the modern professional training of lawyers. The traditional higher education system is not fully capable to provide the need for the training of competitive professionals in the field of jurisprudence. A number of contradictions arise in the way of full-fledged professional training and educational process, among which are the need for the introduction of innovative approaches to the formation of readiness of future lawyers for professional activity and the lack of appropriate models. The purpose of the article is to reveal the trends in the development of the modern legal training of students in higher education institutions, which should be aimed at forming not only professional competencies of modern lawyers, but also, and this is most important – their readiness for personal and professional development, and to determine the role of the discipline “The History of the State and the Law of the Foreign Countries”, to prove the need to apply the latest teaching methods and modern educational electronic learning resources. The tasks of the research are to determine the components of the modern competitive lawyer; to offer innovative forms and methods of teaching the history of the state and the law of foreign countries, oriented to the formation readiness of future specialists for professional activity and professional self-improvement.